PRENATAL FORMATION OF LYMPH NODE SINUSES - Nazarov. B. S.; Qurbonboyeva F. R. (Web of Journals Publishing, 2024)
A progressive transformation of primordia is a common stage in the formation of lymph node sinuses regardless of their localization. A simultaneous formation of the regional reports from the sinus area of the gate through the slit-like rudiments of the intermediate sinuses seems to be the most probable combination.
Keywords: lymph nodes, formation, sinus, lymph node primordium, capsule, popliteal lymph node, pro-interstitial cortikal.